Dynamic evaluation of an in vivo postinflammatory hyperpigmentation model using reflectance confocal microscopy and spectrophotometry. (13th February 2021) - Zhao, Juemin; Liu, Ziqi; Zhang, Chengfeng; Wu, Jiaqiang; Huang, Nan; Du, Yaping; Xiang, Leihong
Abstract: Background: Postinflammatory hyperpigmentation (PIH) reflects a dynamic process from primary injury and cutaneous inflammation to subsequent melanogenesis and hyperpigmentation, of which pathogenesis remains unclear, hindering the development of targeted therapies. Aims: To observe the dynamic development of PIH; determine the starting point and peak point of the inflammatory phase and pigmentary phase; and clarify the timing of anti‐inflammatory and anti‐pigmentary treatment. Methods: Thirty healthy volunteers with Fitzpatrick skin types III‐IV were enrolled and underwent suction blisters. The noninvasive evaluation of inflammation and hyperpigmentation on suction blister sites were performed via spectrophotometry (CM2600d and SIAscope) and RCM for the following 24 weeks. Results: We successfully observed suction blister‐induced PIH lasting over 24 weeks. The inflammatory phase started soon after the procedure and lasted for 8‐12 weeks, manifested by significantly elevated a * values and erythema index detected by spectrophotometry, as well as inflammatory infiltration and angiogenesis shown in RCM images. Meanwhile, melanogenesis was accelerated after week 3 and reached peak on week 8, manifested by significantly accumulated melanin granules and bright pigment rings in different depths under RCM, which was in parallel with elevated melanin index. The darkening skin tone in PIH actually presented a mixture of inflammatory erythema, angiogenesis, and hyperpigmentation. The inflammation and pigmentation phases of PIH were not sequential but partially overlap. Conclusion: The duration of suction blister‐induced PIH is more than 24 weeks. The inflammatory phase partially overlaps with the pigmentary phase, and those drugs with anti‐inflammatory and anti‐pigmentary dual effects are potential choices.